Implementasi Telegram Bot sebagai Media Monitoring Gangguan Pelanggan Telkom dengan Pembaruan Berkala Berbasis Mobile - Noor Arief Kurniawan; Diyah Ruswanti; Astri Charolina (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
In a dynamic operational environment, especially in Telkom customer service, the process of monitoring disturbance reports is a challenge for supervisors. The disturbance reporting applications currently available are web-based, but they have not been designed responsively, so they are less user-friendly when accessed via mobile devices. Meanwhile, supervisors are required to continue conducting direct checks to ensure technician performance in the field. This research aims to develop a mobile-friendly solution in the form of a Telegram Bot that is able to retrieve regularly updated customer disturbance data from a central server, process it, and present it in a concise and easy-to-understand format via the Telegram application. The methods used include periodic data collection by helpdesk officers, data transformation into structured information, and integration of the Telegram API as a user interface. The implementation results indicate that the Telegram bot can provide information on the status of disturbance reports (new, progress, and completed), including the level of urgency, quickly and informatively, according to the latest data available. This solution is proven to support supervisor mobility in decision making and technical supervision without having to rely on web application access via desktop devices. Using Telegram as a platform also increases flexibility in accessing information in various field conditions. This research is a real contribution to the use of bot technology for the efficiency of field monitoring services based on regular updates.